Flexing on Social Media Among Indonesian Teenagers: A Literature Review - Raharja, Hawwin Fitra; Astuti, Tri Marhaeni Pudji; Atmaja, Hamdan Tri; Lestari, Puji (Proceedings of International Conference on Science, Education, and Technology, 2024)
The phenomenon of flexing or showing off one's wealth and lifestyle on social media is increasingly widespread among Indonesian teenagers. This is driven by the desire to gain social recognition and higher social status. This behavior is not only limited to the upper class, but includes all social strata who are trying to meet the demands of an up-to-date lifestyle. This research aims to examine the prevalence of flexing which is characterized by flashy displays and flaunting practices on social media by referring to related literature. The method used in this paper is a rapid literature study using the PICO (Population, Intervention, Comparison, Outcome) approach to search and select relevant studies systematically, ensuring a focused and comprehensive review. From an Islamic perspective, flexing is considered israf (excessive behavior) and is prohibited, as it encourages materialism and shifts the focus from spiritual values ​​to worldly values. From Hindu ethics, especially the teachings of Sapta Timira, which views flexing as a form of darkness that causes individuals to forget their identity and origins, giving rise to negative social impacts. Additionally, flexing impacts people's mental health and trust, as it fosters an environment full of envy and competition. The influence of social media on flexing is enormous, with platforms such as Instagram and Facebook becoming arenas for flaunting luxury, which can lead to criminal activity, such as fraud and money laundering, as seen in the cases of binary options.